2018
DOI: 10.1371/journal.pone.0198394
|View full text |Cite
|
Sign up to set email alerts
|

Antinutritional factors in pearl millet grains: Phytate and goitrogens content variability and molecular characterization of genes involved in their pathways

Abstract: Pearl millet [Pennisetum glaucum (L.) R. Br.] is an important “orphan” cereal and the most widely grown of all the millet species worldwide. It is also the sixth most important cereal in the world after wheat, rice, maize, barley, and sorghum, being largely grown and used in West Africa as well as in India and Pakistan. The present study was carried out in the frame of a program designed to increase benefits and reduce potential health problems deriving from the consumption of pearl millet. The specific goal w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…Furthermore, a recent study on breeding of pearl millet analysed the content of phytic acid and goitrogenic C-glycosylflavones (C-GFs) in pearl millet grains, providing information on genes involved in their biosynthesis. It was shown that large variability existed in both phytic acid and C-GFs contents, implying immense potential for selecting germplasms that are low in these contents, which would help maximize the benefits out of nutrients present in millet-based food [37]. In the current study, pearl millet was included in MDM twice a week and there was no record of developing mineral deficiency or thyroid related problems with the study sample.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, a recent study on breeding of pearl millet analysed the content of phytic acid and goitrogenic C-glycosylflavones (C-GFs) in pearl millet grains, providing information on genes involved in their biosynthesis. It was shown that large variability existed in both phytic acid and C-GFs contents, implying immense potential for selecting germplasms that are low in these contents, which would help maximize the benefits out of nutrients present in millet-based food [37]. In the current study, pearl millet was included in MDM twice a week and there was no record of developing mineral deficiency or thyroid related problems with the study sample.…”
Section: Discussionmentioning
confidence: 92%
“…inbred lines developed at ICRISAT (Niger) from landrace and improved open-pollinated cultivars of West African origin was used in this study together with inbred line ICMB88004 as a control ( S1 Table ). Some of these inbred lines were previously characterized for grain quality [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the putative Pennisetum glaucum (L.) R.Br. (pearl millet) PA-MRP gene has recently been described [34].…”
Section: Pa-mrp Transportersmentioning
confidence: 99%